Decision Making Framework Considering Uncertainty - M. Jagtap Madan, Dr. M. Karande Prasad, Nitin More (International Journal of Advanced Science and Technology, 2020)
Uncertainty is present in the study of science, engineering, medical and social problems. It is not possible to remove uncertainty completely from decision making. We can reduce uncertainty by different methods. This paper explains about various ways to study and analyse uncertainty. It proposes framework to control and reduce uncertainty phenomenon. It is structured as initially reviewed all the reasons for uncertainty presence in a problem starting from definition and classification of uncertainty, then methods applied for handling uncertainties and finally proposed a framework to control and reduce uncertainty in decision making process. Proposed framework is based on study of Researchers those are working on uncertainty since several years.